2022
DOI: 10.1128/spectrum.01134-22
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Comparison of the Abbott SARS-CoV-2 IgG II Quant Assay against Commonly Used Canadian SARS-CoV-2 Enzyme Immunoassays in Blood Donor Retention Specimens, April 2020 to March 2021

Abstract: We describe the qualitative test characteristics of the Abbott SARS-CoV-2 IgG II Quant assay against four other anti-SARS-CoV-2 IgG assays commonly used in Canada. Although there is no gold standard for identifying anti-SARS-CoV-2 seropositivity, aggregate standards can be used to assess seropositivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A large Canadian study of blood donors ( N= 17,428 samples collected between Apr 2020 and Mar 2021) qualitatively compared the agreement of four serological assays including the two used in our analyses (Abbott anti-S, Abbott anti-N, Sinai anti-RBD and Sinai anti-N). 70 They found that the highest agreement of positive Abbott anti-S results was with Sinai anti-RDB results (72·6%) while the lowest agreement was with Abbott anti-N (28·7%). For negative Abbott anti-S results, the agreement was high (>97%) with all assays (being 99·7% for Abbott anti-N negative results).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A large Canadian study of blood donors ( N= 17,428 samples collected between Apr 2020 and Mar 2021) qualitatively compared the agreement of four serological assays including the two used in our analyses (Abbott anti-S, Abbott anti-N, Sinai anti-RBD and Sinai anti-N). 70 They found that the highest agreement of positive Abbott anti-S results was with Sinai anti-RDB results (72·6%) while the lowest agreement was with Abbott anti-N (28·7%). For negative Abbott anti-S results, the agreement was high (>97%) with all assays (being 99·7% for Abbott anti-N negative results).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it is worth mentioning that although we have not performed internal validation tests of the performance of the anti-S IgG assay used in our analysis, several studies 42 , 69 , 75 , 76 used this assay to estimate seroprevalence and a large study with over 17,000 well-characterized blood samples (Canadian blood donors study) has estimated Abbott anti-S IgG sensitivity to be 95·96% (95% CI, 93·27 to 97·63%) and the specificity as 99·35% (95% CI, 99·21 to 99·46%). 70 …”
Section: Discussionmentioning
confidence: 99%
“…This included creating deferral policies for CCP donors who were convalescing after SARS-CoV-2 infection [ 65 ]. Blood operators developed early expertise in characterizing SARS-CoV-2 serological assays [ 10 , 51 , 55 ]. In Canada, this early expertise led to blood operators becoming involved with large SARS-CoV-2 seroprevalence studies and COVID-19 focussed research activities [ 48 ] that still continue into late 2022 [ 10 , 12 , 66 ].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Blood operators developed early expertise in characterizing SARS-CoV-2 serological assays [ 10 , 51 , 55 ]. In Canada, this early expertise led to blood operators becoming involved with large SARS-CoV-2 seroprevalence studies and COVID-19 focussed research activities [ 48 ] that still continue into late 2022 [ 10 , 12 , 66 ]. Understanding the Further development of the role blood operators play in supporting public health is important both to maximise the value of blood services, but also to ensure that blood operators are at the table as national and international pandemic plans are developed and reviewed.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation